Pengaruh Terapi Musik Klasik Mozart pada Pasien Resiko Perilaku Kekerasan di Rumah Sakit Jiwa Aceh - Silvi Ferislan; Fauziah Fauziah; Irma Andriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Aggressive behavior is one of the manifestations commonly found in individuals with mental disorders, and this can potentially cause harm both to themselves and to their surroundings. To address this condition, one non-pharmacological approach that can be implemented is the use of Mozart classical music therapy. This study aims to evaluate the impact of Mozart classical music therapy on patients who have the potential to exhibit violent behavior at Aceh Mental Hospital. The research activities were conducted from July 2 to 5, 2025. The research design adopted in this study is pre-experimental using the One group pretest-posttest Design method. The study subjects consisted of 15 inpatients who had been identified as being at risk for violent behavior, with sample selection carried out through purposive sampling. The findings of the study showed that the average score of signs and symptoms before the intervention was 5.73, with a score range of 3 to 8. After the intervention in the form of Mozart classical music therapy, the average score of signs and symptoms decreased significantly to 1.60, with a range between 1 and 2. Statistical analysis using the Wilcoxon Signed Rank test showed a Z value of -3.437 with a significance level of P = 0.000 (P < 0.05). Based on these results, it can be concluded that Mozart classical music therapy has a significant effect in reducing the risk of violent behavior in patients. Therefore, Mozart classical music therapy is recommended as an effective supportive intervention and can be routinely integrated into psychiatric care rooms.